The Implementation Of Project Based Learning (PjBL) To Improve The Students’ Writing Skill At Seventh Grade Of SMP Swasta YPK Pematang Siantar - Tiodora Fermiska Silalahi; Mardin Silalahi; Rizka Ayuningtya; Julianto T (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
The aim of this research is to find out the implementation Project Based Learning can improve students’ writing skill at SMP Swasta YPK Pematang Siantar. This was a research with quantitative approach. The method in this research was true experimental with pretest-posttest control group design. The samples were 60 students of junior high school, 30 students classified as the experimental group and 30 students as the control group. It was used the writing test for the instrument and the data was analyzed using SPSS 2.6. The results of the data analysis indicate that hypothesis testing of posttest scores, it is found that tcount = 8.973 > ttable = 1,699 at the significance level = 0,05 and degrees of freedom (df) = 29, null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. It means that there are significantly differences on students’ skill by using Project Based Learning (PjBL) and without using Project Based Learning (PjBL) in writing in procedure text at seventh grade of SMP Swasta YPK Pematang Siantar. This is also supported by Sholihah (2017) that Porject Based Learning gives the experience to students discussing and develops their critical thinking. The learning activity also is not teacher centered, because the researcher asked the students to design a plan and record video with the topic they choose. While the students were doing the project, the researcher was monitoring the progress of their project. This project increased the teamwork so that student could be more active in learning activity. After doing the video project, the students asked to write down the procedure text step by step based on the video they made. By doing the project video, the student could understand the process step by step of making a procedure of something, and could improve their writing better directly from the experience